Impact of aging on immunity in the context of COVID-19, HIV, and tuberculosis - Grifoni, Alba; Alonzi, Tonino; Alter, Galit; Noonan, Douglas McClain; Landay, Alan L.; Albini, Adriana; Goletti, Delia (Frontiers in Immunology, 2023)
Knowledge of aging biology needs to be expanded due to the continuously growing number of elderly people worldwide. Aging induces changes that affect all systems of the body. The risk of cardiovascular disease and cancer increases with age. In particular, the age-induced adaptation of the immune system causes a greater susceptibility to infections and contributes to the inability to control pathogen growth and immune-mediated tissue damage. Since the impact of aging on immune function, is still to be fully elucidated, this review addresses some of the recent understanding of age-related changes affecting key components of immunity. The emphasis is on immunosenescence and inflammaging that are impacted by common infectious diseases that are characterized by a high mortality, and includes COVID-19, HIV and tuberculosis.